Employee Performance Analytics - Novikov, Nikolay; Legnerová, Kateřina, 1965-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This Bachelor’s thesis analyses Employee Performance Analytics in corporate environments. The main goal is to examine the implication and implementation of performance evaluation systems and training development in the current corporate structure. The study employs a mixed-methods approach, using a quantitative survey of 34 respondents and qualitative interviews with two representatives from "Curium CZ". This approach provides insights into how employee performance analytics identify and enhance gaps through development programs. The thesis concludes that data-driven strategies’ importance for improving training and fostering continuous learning, is crucial for organisational competitiveness.
Vedoucí práce: Kateřina Legnerová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses